The protection of data subject in case of: A Comparative study of GDPR and Personal Data Protection Act B.E. 2562 - Thograweewong, Kanathip; Kwanyuen, Duangkamol (Rajapark Journal, 2020)
The research aimed to study 1) legal problems in protecting the right of the data subject in case of using digital technology to conduct smart contract 2) elements and conditions of European General Personal Data Protection Regulation (GDPR) and conduct a comparative analysis with Thailand’s Personal Data Protection Act B.E. 2562 3) recommending to amend the law. The methodology of this research is qualitative research by conducting content analysis and comparative analysis of Thai and European Union law The research results were found as follows; 1) electronic transaction Act B.E. 2562 covers the forming of smart contract but does not have provisions to protect right of personal data of consumers who are parties to the contract. 2) Personal Data Protection Act. B.E. 2562 and General Data Protection Act (GDPR) of the European Union does not directly address “Smart contract” but the provision relating to the condition of data processing by which the consent of data subject is required could be applied to protect the right of the data subject. However, the provision has limitations and does not cover the right to object or refuse to enter the smart contract. 3) General Data Protection Act (GDPR) of the European Union has a specific provision on “Automated individual decision-making” in article 22 which could be interpreted to cover smart contract, i.e., the data subject has the right not to be subject to the smart contract in which a decision based solely on automated processing. However, the Personal Data Protection Act. B.E. 2562 does not have this specific article. Consequently, the research proposes the amendment of this Act in include provision on “Automated individual decision-making” as modeled in article 22 of GDPR.